Inter-observer agreement in GTV delineation of bone metastases on CT and impact of MR imaging: A multicenter study. Issue 3 (March 2018) - Gerlich, A.S.; van der Velden, J.M.; Kotte, A.N.T.J.; Tseng, C.L.; Fanetti, G.; Eppinga, W.S.C.; Kasperts, N.; Intven, M.P.W.; Pameijer, F.A.; Philippens, M.E.P.; Verkooijen, H.M.; Seravalli, E.
Abstract: Background and purpose: The use of Stereotactic Body Radiotherapy (SBRT) for bone metastases is increasing rapidly. Therefore, knowledge of the inter-observer differences in tumor volume delineation is essential to guarantee precise dose delivery. The aim of this study is to compare inter-observer agreement in bone metastases delineated on different imaging modalities. Material and methods: Twenty consecutive patients with bone metastases treated with SBRT were selected. All patients received CT and MR imaging in treatment position prior to SBRT. Five observers from three institutions independently delineated gross tumor volume (GTV) on CT alone, CT with co-registered MRI and MRI alone. Four contours per imaging modality per patient were available, as one set of contours was shared by 2 observers. Inter-observer agreement, expressed in generalized conformity index [CIgen], volumes of contours and contours center of mass (COM) were calculated per patient and imaging modality. Results: Mean GTV delineated on MR (45.9 ± 52.0 cm 3 ) was significantly larger compared to CT–MR (40.2 ± 49.4 cm 3 ) and CT (34.8 ± 41.8 cm 3 ). A considerable variation in CIgen was found on CT (mean 0.46, range 0.15–0.75) and CT–MRI (mean 0.54, range 0.17–0.71). The highest agreement was found on MRI (mean 0.56, range 0.20–0.77). The largest variations of COM were found in anterior–posterior direction for all imaging modalities. Conclusions: Large inter-observer variation in GTV delineation exists for CT, CT–MRI and MRI. MRI-based GTV delineation resulted in larger volumes and highest consistency between observers.